2021
DOI: 10.1371/journal.pone.0259828
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and environmental determinants of acute diarrhea among under-five children from public health facilities of Siyadebirena Wayu district, north Shoa zone, Amhara regional state, Ethiopia: Unmatched case-control study

Abstract: Background Acute diarrhea is a major public health problem in the world. Next to pneumonia, it is the leading cause of death in children under five years old. Globally, even though childhood diarrhea disease kills millions, the interaction of socio-demographic, behavioral, and environmental factors of acute diarrhea in children aged 6–59 months is not investigated yet in the current study area. Objective To determine behavioral and environmental predictors of acute diarrhea among under-five children from pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…3 It is spread through contaminated food or drinking water or from person to person due to poor hygiene. 4 Diarrhoea among children under 5 years is a central public health issue worldwide. 5 It causes more than 1.7 billion cases and kills 525 000 children under 5 years old each year, making it the world's second leading cause of mortality among children under 5 years.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…3 It is spread through contaminated food or drinking water or from person to person due to poor hygiene. 4 Diarrhoea among children under 5 years is a central public health issue worldwide. 5 It causes more than 1.7 billion cases and kills 525 000 children under 5 years old each year, making it the world's second leading cause of mortality among children under 5 years.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Diarrhoea is typically a sign of an infection in the gastrointestinal tract, which can be brought on by several bacterial, viral and parasitic species 3. It is spread through contaminated food or drinking water or from person to person due to poor hygiene 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diarrhea is a condition where the body experiences an increase in the volume, looseness, and abnormal frequency of defecation, i.e., more than 3 times among adults and more than 4 times among newborns without the presence of blood in the stool [1]. Effective treatment of diarrhea can minimize its severity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in Ethiopia have identified many factors that are associated with childhood diarrhea. These factors include: child's age [6][7][8][9][10], place of residency [11][12][13], lack of exclusive breastfeeding [14][15][16][17], unvaccinated against rotavirus [7,14,[18][19][20][21][22], undernutrition [23][24][25], limited maternal education [11,23,24,26], inadequate knowledge about diarrheal disease [8,27], poor handwashing practices [15,24,28,29], low wealth status [14,26,27,30,31], unimproved sources of drinking water [6,9,12,13,19,32], and unimproved toilet facilities [7,19,20,[32][33]…”
Section: Introductionmentioning
confidence: 99%